Penggunaan Media Pembelajaran Mozaik Terhadap Kreativitas Siswa Pada Mata Pelajaran Seni Budaya dan Prakarya di Kelas IV SD Negeri 5 Pedamaran - Laksana, Robert Budi; Anugrah, Adelia Septa; Hetilaniar, Hetilaniar (Universitas Batanghari Jambi, 2023)
The purpose of this study was to determine the use of mosaic learning media for student creativity in arts, culture and crafts subjects in grade IV SD Negeri 5 Pedamaran. Types of qualitative descriptive research. The data sources used are primary data sources and secondary data. Observation, interview and documentation data collection techniques. Data analysis techniques are carried out by data reduction, data presentation and conclusions. The results of the research analysis show that the use of mosaic learning can affect students' creativity when learning fine arts, almost all students have great curiosity, often ask weighty questions, are able to express spontaneous opinions and are not shy, have their own opinions and can express them, can work alone and like to try new things, but there are only a few students who give a lot of ideas and suggestions for a The problem in learning, students also cannot do the mosaic task themselves because students still need guidance from the teacher, there are still many students who ask questions when making mosaic works takes place. However, students can complete mosaic works by themselves, students are also very happy with mosaics, students can create works with their own creative ideas.